STUDI DISTRIBUSI TEMPERATUR PERMUKAAN DANGKAL, EMISI GAS KARBONDIOKSIDA DAN POLA ALIRAN FLUIDA UNTUK MENGKLARIFIKASI SISTEM PANAS BUMI DI DAERAH MANIFESTASI DIWAK-DEREKAN, JAWA TENGAH - Imroatun Nikmah; Udi Harmoko (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
The research on temperature, carbon dioxide emissions (CO2) and fluid flow has been done at the site of geothermal manifestations Diwak-Derekan by using three methods: shallow surface temperature method, emissions of carbon dioxide (CO2) and Advance Groundwater (water level). The purpose of this study is to determine the temperature distribution, the emission of carbon dioxide (CO2) and fluid flow in the area Diwak-Derekan to get a conceptual model of the geothermal system.The shallow surface temperature measurement, emissions of carbon dioxide (CO2) and water table at the site of geothermal manifestations Diwak-Derekan has done with maps and put them in a third compiles data on height topography data.The result of study, in the manifestation area obtained result distribution of shallow surface temperature is about 30,77 oC (Diwak) and 30,64 oC (Derekan) with emission of carbon dioxide (CO2) is about 9%. And for water level measurement indicates that the flow of shallow ground water is coming from the west location of manifestations and mixed with hydrothermal fluids which then turn up to the surface as hot springs.Keywords: shallow surface temperatures, emissions of carbon dioxide (CO2), ground water, geothermal.